Pengaruh Gaya Kepemimpinan Dan Komunikasi Interpersonal Terhadap Produktivitas Karyawan - Yuli Mindarti; Abdul Kodir Djaelani; Muhammad Ridwan Basalama (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this research are 1) To describe the leadership style, interpersonal communication and employee’s productivity of Company X. 2) The effect of leadership style to employee’s productivity of Company X, 3) The effect of interpersonal communication to employee’s productivity of Company X, 4) The effect of leadership style and interpersonal communication to employee’s productivity of Company XThis research is using quantitative method with descriptive approach and conducted at Company X with population 205 employees, however it is simplified using Slovin formula to 67 people. Data collection technique used questionnaire with likert scale measurement. Analytical technique used are validity, reliability, normality, regression analysis double linier, multicollinearity, heteroscedasticity, hypothesis F, hypothesis t, and coefficient of determinationThe result shows that: 1) leadership style does a significant effect to employee’s productivity, 2) interpersonal communication does a significant difference to employee’s productivity, 3) leadership style and interpersonal communication does simultantly significant to employee’s productivity of Company X. Keywords: Leadership stlye, interpersonal communication, productivity